(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the speech strategies and tactics of Kazakh lawyer Igor Vranchev based on the material of his speeches in court on charges against citizen Bishimbayev, which received a wide public response in Kazakhstan. The present study analyzes the speech strategies and tactics of lawyer I.Vranchev used in the trial. The analysis showed that the lawyer used various strategies and tactics to achieve his communicative goal. This is a strategy of discrediting the accused, a strategy of emotional impact, a strategy of opposition, a strategy of audience engagement, and a strategy of credibility and credibility. The lawyer used manipulative speech strategies, actively using emotional, rhetorical and defamatory tactics, and emphasized the contrast between the external situation and reality. There is no neutrality in his speech — it is aimed at creating a strong emotional rejection of the accused among the listeners and convincing them of his complete guilt. In the course of our research, it was found that the communicative goal of lawyer I.Vranchev has an emotional and evaluative component; his statements are aimed at forming an emotionally negative attitude towards the accused among listeners. It can be unequivocally stated that the speech strategies and tactics used by him achieved their intended goal.